Steroid Injection as an Effective Treatment for Lateral Epicondylitis - Saad Riaz, Imtiaz Ahmed Shakir, Nadeem Kashmiri, Shehzad Anjum, Nayyar Qayyum (Journal of Rawalpindi Medical College, 2017)
Methods: In this case control study 70 patients with lateral epicondylitis with no previous history of trauma, surgery around elbow joint or previous history of steroid injection were included. Patients were given local steroid injection after preparing the area with an antiseptic solution. The most tender point was localized and 40 mg methyl-prednisolone solution mixed with one ml of 2% xylocaine solution was infiltrated. Patients were followed up at six weeks for the evaluation of global improvement in symptoms using Likert-type scale. Results:The mean age of the sample was 43 years. 42 patients were in the age group of 41-50 years. Majority (81.4%) patients were females. Most of the patients (81.4%) scored 1 and 2 on Linkert type scale, showing global improvement. Nine patients improved with the second dose of steroid injection making cumulative efficacy to 94%. Conclusion: Local steroid infiltration is an effective method of relieving pain and improving function in patients with tennis elbowBackground: To determine efficacy of local steroid infiltration in patients with lateral epicondyliti